2021
DOI: 10.1111/bcp.15105
|View full text |Cite
|
Sign up to set email alerts
|

Saliva as a sampling matrix for therapeutic drug monitoring of gentamicin in neonates: A prospective population pharmacokinetic and simulation study

Abstract: Therapeutic drug monitoring (TDM) of gentamicin in neonates is recommended for safe and effective dosing and is currently performed by plasma sampling, which is an invasive and painful procedure. In this study, feasibility of a non-invasive gentamicin TDM strategy using saliva was investigated.Methods: This was a multicentre, prospective, observational cohort study including 54 neonates. Any neonate treated with intravenous gentamicin was eligible for the study. Up to eight saliva samples were collected per pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
3
8
0
Order By: Relevance
“…Thus, it seems that low detection limits of the quantification method is essential for the development of a saliva TDM method of aminoglycosides. We have previously investigated and reported that gentamicin is distributed in the saliva of NICU admitted neonates with (suspected) early‐onset sepsis 7 . Moreover, gentamicin PK in plasma and saliva was described and TDM using 4 saliva samples was shown to be feasible, with a pTA of 81%, similar to our findings for amikacin as reported in the present study.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Thus, it seems that low detection limits of the quantification method is essential for the development of a saliva TDM method of aminoglycosides. We have previously investigated and reported that gentamicin is distributed in the saliva of NICU admitted neonates with (suspected) early‐onset sepsis 7 . Moreover, gentamicin PK in plasma and saliva was described and TDM using 4 saliva samples was shown to be feasible, with a pTA of 81%, similar to our findings for amikacin as reported in the present study.…”
Section: Discussionsupporting
confidence: 88%
“…This finding is evident when comparing the salivary amikacin PK profile of premature and term neonates, as depicted in Figure 2. The aforementioned findings demonstrate high similarities to our previous study with gentamicin, as the final model structure is near identical 7 . Moreover, results from that study also suggested that higher salivary gentamicin levels are present in premature neonates, when compared to term neonates, possibly reflecting differences in blood/saliva barrier development.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…8 Thus, measuring concentrations of molecules directly in undiluted saliva can prove transformative in the early detection and diagnostic of diseases to support decision-making in treatments. 1,4,9,10 Current techniques for salivary molecular measurements rely on high-performance liquid chromatography 11−14 and immuno or lateral flow assays. 15−21 Despite their high accuracy and sensitivity, chromatographic methods and immunoassays require cumbersome, laboratory-bound, and expensive instru-ments operated by trained personnel to only provide a single snapshot of one's health hours to days after sample collection, 22,23 which ultimately causes delayed diagnostics and higher analysis costs.…”
mentioning
confidence: 99%
“…Saliva, in contrast, through natural drooling, can be collected with minimal effort and discomfort from patients, thus offering an alternative biological matrix. In a clinical setting, saliva has been reported to be informative as it contains biomarkers with highly correlated concentrations to ones measured in blood . Thus, measuring concentrations of molecules directly in undiluted saliva can prove transformative in the early detection and diagnostic of diseases to support decision-making in treatments. ,,, …”
mentioning
confidence: 99%